The ring and the street: young immigrant boxers in the Bolognina neighbourhood of Bologna. Issue 3 (August 2015) - Scandurra, Giuseppe
Abstract : This article describes the social organisation of the 'Tranvieri' boxing gym in Bolognina, a working-class neighbourhood of Bologna that has been rapidly changing over the last 20 years due to the closure of factories and the arrival of immigrants, especially from the Maghreb. The gym population has changed accordingly: currently about two-thirds of those attending the gym as a leisure centre have immigrant parents. The author studied the everyday life of these young boxers, born in Italy but without citizenship, who visit the gym daily after finishing vocational school, work and family responsibilities. For them, boxing is not a solution to the frustration inflicted by a society they perceive as indifferent if not hostile towards them, but it does offer them the possibility of not being represented as persons excluded from that society.